Long noncoding RNA00324 is involved in the inflammation of rheumatoid arthritis by targeting miR‐10a‐5p via the NF‐κB pathway - Binbin Xie; Faquan Lin; Wei Bao; Yangyang Zhang; Yi Liu; Xiaohui Li; Wei Hou; Qiyan Zeng (Immunity, Inflammation and Disease, 2023)
Abstract Background Altered expressions of genes in immune cells and synovial tissues are involved in the pathology of rheumatoid arthritis (RA). Long noncoding RNAs act as competing endogenous RNAs and can cause immune disorders. The goal of this study was to reveal the association between noncoding RNA linc00324 and RA, and a plausible action mechanism was proposed. Methods RT‐qPCR was used to evaluate the expression of linc00324 in peripheral blood mononuclear cells isolated from 50 RA patients and 50 healthy controls, and the correlations between linc00324 level and the clinical indicators were analyzed. Flow cytometry was used to characterize CD4+ T cells. The effects of linc00324 on cytokine production and cell proliferation of CD4+ T cells were evaluated by ELISA assay and Western blot. The interaction between linc00324 and miR‐10a‐5p was investigated by RNA immunoprecipitation and dual‐luciferase assays. Results The linc00324 expression was significantly enhanced in RA patients, and linc00324 expression was positively correlated with rheumatoid factor and CD4+ T cells. Overexpression of linc00324 promoted CD4+ T cells proliferation, and enhanced chemokine MIP‐1α secretion and NF‐κB phosphorylation level, whereas knockout of linc00324 blocked CD4+ T cell proliferation and NF‐κB phosphorylation. Overexpression of miR‐10a‐5p led to the decrease of CD4+ T cells proliferation and NF‐κB phosphorylation, and reversed the effects of linc00324 on cell proliferation and NF‐κB activity. Conclusion Linc00324 was upregulated in RA and may exaggerate inflammation by targeting miR‐10a‐5p through NF‐κB signaling pathway.